The Role of Society in the Trauma Chronization: The Outcomes of War Experiences in Serbia - Čavić-Đurić, Tamara M. (Sociološki pregled, 2019)
Introduction: Тhe consequences of wars are reflected on the individual, family and collective plans.Aim: To perceive social mechanisms that shape the chronic course of posttraumatic reactions and to propose preventive measures and therapeutic procedures.Method: A review of publications on the outcomes of war experiences among soldiers, prisoners, refugees and civilians in Serbia after the wars on the territory of the former SFRY and the bombing of the FRY.Results: The lack of social integration among victims of war triggers the chronization of post-traumatic stress disorder, increased violence and depression.Conclusion: Social reparation can prevent the complication of posttraumatic disorders and different forms of group psychotherapy are a cure of choice for these conditions.Keywords: post-war society, war, psychological trauma, social isolation, posttraumatic stress disorder, group psychotherapy